Paternity leave and father's involvement in the care of an infant: Time diary evidence from Australia - Hosking, A; Whitehouse, G; Baxter, Janeen (My University, 2008)
Much of the debate around parental leave policies has focused on the extent to which their usage challenges or consolidates gendered patterns of paid and unpaid work, with recent analyses concerned with the propensity of fathers to take leave and the effects of fathers' leave taking on gendered divisions of household labour. In this paper, we explore whether Australian fathers' use or duration of leave around a child's birth is associated with father's involvement in parental care when the child reaches age 4 to 17 months. We draw on detailed time-diary data collected for infants at wave 1 of the Longitudinal Survey of Australian Children (LSAC) in 2004. We examine how long infants are with their father from 7am - 8pm and how much of this time is taken up by the routine tasks of physical care (bath, nappy change, dress, feeding, drinking and eating) and interactive care (held, cuddled, soothed, read, talked to, sung to and where the infant is crying or upset). Regression results show that fathers who took no leave or a short leave of up to one week around the birth do not spend any less time with an infant on either of our measures than fathers who took a long period of leave lasting three weeks or more. Infants' time in their father's care with the mother absent is found to be significantly lower where the father works long hours and significantly higher where the mother is working full-time or long part-time hours.
Keywords: Employment; Families; Employment -- Parental leave; Families -- Fathers; Labour market; Families and relationships; Employment; Families; Parental leave; Fathers; Families and relationships; Employment and unemployment